2009
DOI: 10.1021/bi901786x
|View full text |Cite
|
Sign up to set email alerts
|

The Uremic Toxin 3-Indoxyl Sulfate Is a Potent Endogenous Agonist for the Human Aryl Hydrocarbon Receptor

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor involved in the regulation of multiple cellular pathways, such as xenobiotic metabolism and Th17 cell differentiation. Identification of key physiologically relevant ligand(s) that regulate AHR function remains to be accomplished. Screening of indole metabolites has identified indoxyl-3-sulfate (I3S) as a potent endogenous ligand that selectively activates the human AHR at nanomolar concentrations in primary human hepatocytes, regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
227
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(240 citation statements)
references
References 43 publications
(80 reference statements)
4
227
1
Order By: Relevance
“…At present, kynurenine, kynurenic acid, indoleacetic acid, and indoxyl sulfate-all indolic products of tryptophan metabolism-have been shown to bind to the AhR or induce the expression of AhR response genes, such as CYP1A1. 38,[93][94][95][96][97] Moreover, as shown in Table 3, all four metabolites activate the AhR at concentrations either similar to the highest C max determined in dialysis patients (eg, indole acetic acid) or at levels decisively lower than the C max , for instance indoxyl sulfate. To date, the clinical implications of AhR activation in the setting of CKD development and progression remain unclear, however, it has been postulated that uremic solutes might evoke dioxinlike toxicity, 38 leading to suppression of immune responses, induction of carcinogenesis and accelerating tumor growth, and promoting atherosclerosis.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 83%
“…At present, kynurenine, kynurenic acid, indoleacetic acid, and indoxyl sulfate-all indolic products of tryptophan metabolism-have been shown to bind to the AhR or induce the expression of AhR response genes, such as CYP1A1. 38,[93][94][95][96][97] Moreover, as shown in Table 3, all four metabolites activate the AhR at concentrations either similar to the highest C max determined in dialysis patients (eg, indole acetic acid) or at levels decisively lower than the C max , for instance indoxyl sulfate. To date, the clinical implications of AhR activation in the setting of CKD development and progression remain unclear, however, it has been postulated that uremic solutes might evoke dioxinlike toxicity, 38 leading to suppression of immune responses, induction of carcinogenesis and accelerating tumor growth, and promoting atherosclerosis.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 83%
“…In 2010, Schroeder et al demonstrated that the aryl hydrocarbon receptor (AhR) is an endogenous receptor for indoxyl sulfate 24) . AhR is a member of the basic helix -loop -helix Per -Arnt -Sim regulatory protein superfamily.…”
Section: Laboratory Animalsmentioning
confidence: 99%
“…14,15 Several endogenous chemicals, including IS, bind to and activate the AHR. 12,16 Therefore, we hypothesized that IS accumulation in CKD patients induces TF through an AHR pathway, thus potentiating thrombosis. Our results demonstrate that the AHR regulates baseline and IS-mediated vSMC TF levels and activity and show the feasibility of targeting this AHR pathway with novel competitive AHR antagonists able to modify CKD-specific thrombotic risk.…”
mentioning
confidence: 99%